Development of Liewik, academic software, for problem solving in physics - Maano, M. K. S. (Animo Repository, 2022)
This research study was focused on the development of Liewik: Academic Software for Developing Problem Solving Skills that will improve the problem solving competencies of students and will serve as framework of software design. In this study, the development of Liewik followed the recommendations of various local and foreign Physics Education Researchers regarding problem solving in Physics and technology integration in education found as unpublished materials and retrieved from the World Wide Web. Moreover, suggestions regarding technical aspects from computer programmers were considered in the development of the running Liewik program. Evaluation shows that LIEWIK can be used for teaching and developing problem solving skills and may be used as model to develop the same for other lessons in Physics.